Penerapan Model Pembelajaran Numbered Head Together Berbantu Permainan Ular Tangga Untuk Peningkatan Hasil Belajar Siswa - Merna Yunia Artha; Mohammad Kanzunnudin; Imaniar Purbasari (PGSD Universitas Muria Kudus, 2021)
The purpose of this study is to describe the improvement of student learning outcomes on the theme of My Living Area in the fourth grade of SD 3 Panjang with the application of the Numbered Head Together (NHT) learning model assisted by Snakes and Ladders media.The research method used is classroom action research which was carried out in class IV SD 3 Panjang with 16 students as research subjects which lasted for two cycles, each cycle consisting of two meetings. The dependent variables in this study are the Numbered Head Together learning model and Snakes and Ladders Game media, while the dependent variable is student learning outcomes on the Regional Theme I Live in and the teacher's teaching skills on the Regional Theme where I live. Data collection methods in the form of tests, observations, interviews, and documentation. The data obtained from the actions taken were analyzed quantitatively and qualitatively.The results showed that the use of the Numbered Head Together learning model with the help of the snake and ladder game could improve student learning outcomes on the theme of the area where I live, social studies content and Indonesian language for class IV SD 3 Panjang from an average social studies score of 37.5%, Indonesian language 43.75% before The research was conducted to find the average score for social studies was 62.5%, Indonesian language was 56.3% in the first cycle and improved even more in the second cycle with an average social studies score of 81.25%, Indonesian 75% from the KKM 70.